Áreas potenciais para a criação de unidade de conservação no município de Marechal Cândido Rondon, Paraná - Mosconi, Luciane (2018)
The natural ecosystems are important for the maintenance of biodiversity and environmental services. These are also fundamental for quality of human life. On the other hand, it seems that human beings do not understand this reality and fail to take care of what is important to us. For example, the forest ecosystems of the Atlantic Forest biome are becoming rarer due to the intense changes caused by man. In this biome, in the ecoregion known as Interior Atlantic Forest, remain less than 3% of the natural forest area, with steady decline. Due to the need to conserve natural resources, the Treaty of Aich (Japan) was established. In document the signatory nations, which include Brazil, have determined that at least 17% of their terrestrial ecosystems are in Conservation Units (UC) by the year 2020. For this, innovative initiatives established, such as the Payment for Environmental Services, in the state of Paraná, with the Ecological ICMS. Part of the ICMS collected by the state return to the municipalities that consolidate some type of UC. Even with this financial stimulus, many municipalities still deprived of UC, as is the case of Marechal Cândido Rondon. To solve this problem, it is important to check if there are potential areas for the creation of UC. For this, it was necessary to evaluate the existence of forest remnants and to delimit the forest fragments in the territory of this municipality. In addition, the importance of these forest fragments in the regional context of biodiversity conservation analyzed; identify their structure and the functional connectivity between them; to verify the type of existing rural property and the interest of its owners in the creation of UC. With the analysis of satellite images from 1978, 2012-2014, it was possible to identify 2,118 hectares (ha) of forest remnants and 14,039 ha of secondary forests, which together make up 16,157 ha (21.6% municipal territory) of Interior Atlantic forest fragments. As to the distribution, structure and functionality of these forest fragments, it found that the greatest area of coverage, quantity and continuous areas of forest fragments are in the river basins of the Marreco and São Francisco Verdadeiro rivers. Through technical documents and environmental conservation laws it was possible to evaluate the importance of these forest fragments, in a regional and national context, and to affirm that some of these areas are potential areas for biodiversity conservation and establishment of UC. The interviews allowed know the land structure and the opinion of farmers regarding the constitution of UC in their properties, being the majority of the small rural properties, of private domain and with the farmers that agree with the possibility of creating UC in their areas. In summary, the analysis of Federal and State Laws and technical documents, which deal with the conservation of biodiversity, allowed to consider that, for the areas indicated as potential for creation of UC, the category that best suits are the RPPN.